2010
DOI: 10.1007/s00441-010-1011-7
|View full text |Cite
|
Sign up to set email alerts
|

Lung tissue regeneration after induced injury in Runx3 KO mice

Abstract: Runx3 is essential for normal murine lung development, and Runx3 knockout (KO) mice, which die soon after birth, exhibit alveolar hyperplasia. Wound healing, tissue repair, and regeneration mechanisms are necessary in humans for proper early lung development. Previous studies have reported that various signaling molecules, such as pErk, Tgf-beta1, CCSP, pJnk, Smad3, and HSP70 are closely related to wound healing. In order to confirm the relationship between lung defects caused by the loss of function of Runx3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In many cases, these studies are still at the in vitro stages, such as the use of vimentin to improve wound repair [30], or just suggest a possible beneficial role (e.g., connexins [31], adrenomedullin [32] or a possible modulation of the transcription factors, FoxM1 and Runx3 [33,34]) and need further research to prove their viability in vivo . Improvement of plasma membrane repair is a possible direct treatment.…”
Section: Therapeutic Strategies Aimed At Lung Repairmentioning
confidence: 99%
“…In many cases, these studies are still at the in vitro stages, such as the use of vimentin to improve wound repair [30], or just suggest a possible beneficial role (e.g., connexins [31], adrenomedullin [32] or a possible modulation of the transcription factors, FoxM1 and Runx3 [33,34]) and need further research to prove their viability in vivo . Improvement of plasma membrane repair is a possible direct treatment.…”
Section: Therapeutic Strategies Aimed At Lung Repairmentioning
confidence: 99%
“…In many cases, these studies are still at the in vitro stages, such as the use of vimentin to improve wound repair [30], or just suggest a possible benefi cial role (e.g., connexins [31], adrenomedullin [32] or a possible modulation of the transcription factors, FoxM1 and Runx3 [33,34]) and need further research to prove their viability in vivo. Improvement of plasma membrane repair is a possible direct treatment.…”
Section: Therapeutic Strategies Aimed At Lung Repairmentioning
confidence: 99%
“…RUNX3 is an important target of the TGF-β signaling pathway (24) and an inhibitor of the Wnt pathway (25,26). Previous studies have revealed that the central role of RUNX3 in tumor formation may be associated with its developmental significance (27,28). The major reason for the lost or decreased expression of RUNX3 is hypermethylation of the RUNX3 proximal promoter CpG island, which is involved in the formation of a number of cancer types, including breast (29), gastric (30,31) and colon cancer (32,33).…”
Section: Discussionmentioning
confidence: 99%